A Note on Aoki's Perfect Controllability of a Linear Macro-Economic Model - Uebe, G. (Review of Economic Studies, 1977)
Journal Article A Note on Aoki's Perfect Controllability of a Linear Macro-economic Model Get access G. Uebe G. Uebe Technische Universität München Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 44, Issue 1, February 1977, Pages 191–192, https://doi.org/10.2307/2296986 Published: 01 February 1977 Article history Received: 01 July 1975 Accepted: 01 April 1976 Published: 01 February 1977